2021
DOI: 10.1016/j.btre.2021.e00621
|View full text |Cite
|
Sign up to set email alerts
|

Identification, characterization, and lipid profiling of microalgae Scenedesmus sp. NC1, isolated from coal mine effluent with potential for biofuel production

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 52 publications
0
6
0
2
Order By: Relevance
“…as described in Figure 3 . Scenedesmus belongs to Scenedesmaceae family, which are already reported as a probable source for biofuel production in recent years with limited information ( Pancha et al, 2015 ; Tripathi et al, 2015 ; Kumar et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…as described in Figure 3 . Scenedesmus belongs to Scenedesmaceae family, which are already reported as a probable source for biofuel production in recent years with limited information ( Pancha et al, 2015 ; Tripathi et al, 2015 ; Kumar et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Microalgae are known to produce economically beneficial substances such as amino acids, polysaccharides, carbohydrates, proteins, and fatty acids during sewage treatment processes [31]. In this study, we found that the differentially accumulated metabolites were most significantly enriched in KEGG pathways to alanine, aspartate, glutamate, arachidonic acid, and riboflavin metabolisms, fatty acid biosynthesis, and fatty acid degradation.…”
Section: Discussionmentioning
confidence: 61%
“…Microalgae are known to produce economically beneficial substances such as amino acids, polysaccharides, carbohydrates, proteins, and fatty acids during sewage treatment processes [31].…”
Section: Changes In Primary Metabolites Related To Sewage Treatmentmentioning
confidence: 99%
“…An interesting autoflocculating microalgal strain, Scenedesmus sp. NC1, was isolated by Kumar et al [ 240 ] from coal mine effluent wastewater. Its lipid characterization exhibited a complex profile (18.55% monounsaturated, 22.74% polyunsaturated, and 35.15% saturated fatty acids), designating this strain as a prospective candidate for biodiesel production.…”
Section: Coal Microalgae Hold Great Biotechnological Potential In Coa...mentioning
confidence: 99%